ALTERATION OF OPTICAL DENSITY OF ALVEOLAR RIDGE ON RATS’ JAWS AND ITS CORRECTION UNDER EFFECT OF SALTS OF HEAVY METALS - Lakhtin, Yu.V. (World of Medicine and Biology, 2012)
Optical density of alvolar ridge on rats’ jaws was investigated under effect of salts of heavy metals. It was established that bone mineral density declined under the effect of salts of heavy metals. Administration of alpha lipoic acid contributed to reduction of negative impact of heavy metals on the bone and to its densification.
Keywords: alveolar ridge; jaws; salts of heavy metals; alpha lipoic acid